Analysis of financial literacy level of civil servants in Padang City - Amelia Gustina Leodi (Financial Management Studies, 2021)
The purpose of this study was to determine how the level of financial literacy in civil servants in the city of Padang. This research is a quantitative research using descriptive method. The population in this study, namely Civil Servants in Padang City, found 9,030 people. The number of samples in this study were 130 people using a non-probability purposive sampling technique. The results of this study indicate that the level of financial literacy in Civil Servants in Padang City is high with a score of 4.38 (88%); general knowledge with a score of 4.63 (93%); saving and borrowing 4.03 (81%); insurance with a score of 4.48 (90%); and investment with a score of 4.36 (87%).